2013
DOI: 10.1063/1.4813486
|View full text |Cite
|
Sign up to set email alerts
|

Band gap and structure of single crystal BiI3: Resolving discrepancies in literature

Abstract: Bismuth tri-iodide (BiI3) is an intermediate band gap semiconductor with potential for room temperature gamma-ray detection applications. Remarkably, very different band gap characteristics and values of BiI3 have been reported in literature, which may be attributed to its complicated layered structure with strongly bound BiI6 octahedra held together by weak van der Waals interactions. Here, to resolve this discrepancy, the band gap of BiI3 was characterized through optical and computational methods and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

20
107
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(130 citation statements)
references
References 32 publications
20
107
2
1
Order By: Relevance
“…Incorporating spin-orbit coupling, we compute the indirect bandgap of BiI 3 (R3) to be 1.73 eV (2.51 eV without spin-orbit interactions), which agrees well with earlier DFT results. 8 We determine the fractional density of states in the valence and conduction bands, separated by atomic and orbital contributions. In Fig.…”
mentioning
confidence: 99%
“…Incorporating spin-orbit coupling, we compute the indirect bandgap of BiI 3 (R3) to be 1.73 eV (2.51 eV without spin-orbit interactions), which agrees well with earlier DFT results. 8 We determine the fractional density of states in the valence and conduction bands, separated by atomic and orbital contributions. In Fig.…”
mentioning
confidence: 99%
“…From both measurement modes, the band gap was determined to be approximately 1.8 eV assuming an indirect gap, which is well within the range of values reported previously. 20 The band structure presented in the following illustrates that the direct and indirect transition lie very close together. The ionization energy (I), which is the position of the valence band maximum (VBM) with respect to the vacuum energy, was determined experimentally from UPS (Fig-FIG.…”
mentioning
confidence: 99%
“…14,15,19 More recently, the transition at room temperature has been assigned to an indirect gap by optical absorption spectroscopy. 20 Density functional theory (DFT) has been previously used to elucidate the electronic band structure of BiI 3 and confirm the indirect nature of the transition, 20,21 but only few recent studies 5,[20][21][22] apply spin orbit coupling, a) Electronic mail: alehner@mrl.ucsb.edu which is necessary in 6s systems. 16,17 Most of those studies have been limited by the choice of using DFT within the local density approximation (LDA) or the generalized gradient approximation (GGA), which are known for poorly reproducing the band gaps of semiconductors.…”
mentioning
confidence: 99%
“…61 Through optical absorption measurements, an indirect bandgap at 1.67-1.73 eV has been observed. 61 Measuring single crystals grown by an electrochemical gradient vertical Bridgman method, Brandt et al reported a photoluminescence emission centred at 1.85 eV. 37 From time-resolved photoluminescence measurements, they estimated a minority carrier lifetime of 1.3-1.5 ns.…”
mentioning
confidence: 99%
“…37,61,62 Due to the indirect nature of the bandgap resulting in a low absorption coefficient near the band edge (10 2 cm 1 ), measurements by ellipsometry have resulted in an overestimation of the bandgap where the direct transition was probed (∼1.9 eV). 61 Through optical absorption measurements, an indirect bandgap at 1.67-1.73 eV has been observed. 61 Measuring single crystals grown by an electrochemical gradient vertical Bridgman method, Brandt et al reported a photoluminescence emission centred at 1.85 eV.…”
mentioning
confidence: 99%